2017
DOI: 10.1111/liv.13633
|View full text |Cite
|
Sign up to set email alerts
|

The association between steatosis and diabetes with hepatocellular carcinoma in non‐genotype 3 chronic hepatitis C patients

Abstract: Steatosis and DM may be associated with HCC development in non-genotype 3 CHC patients with SVR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…77,78 Co-existing fatty liver is also a risk factor for Kawaguchi T et al P. 8 HCC after cure in patients with HCV infection. 79,80 Furthermore, Peleg et al demonstrated that fatty liver is a major predictor of all-cause mortality in patients who achieve a sustained virological response following DAA treatment, regardless of fibrosis stage. 81 Thus, MAFLD should be treated and managed on its own merits, even in patients with cured HCV infection.…”
Section: Importance Of Multiple Etiologies Of Liver Disease: Mafld Viral Hepatitis and Alcoholic Intakementioning
confidence: 99%
See 1 more Smart Citation
“…77,78 Co-existing fatty liver is also a risk factor for Kawaguchi T et al P. 8 HCC after cure in patients with HCV infection. 79,80 Furthermore, Peleg et al demonstrated that fatty liver is a major predictor of all-cause mortality in patients who achieve a sustained virological response following DAA treatment, regardless of fibrosis stage. 81 Thus, MAFLD should be treated and managed on its own merits, even in patients with cured HCV infection.…”
Section: Importance Of Multiple Etiologies Of Liver Disease: Mafld Viral Hepatitis and Alcoholic Intakementioning
confidence: 99%
“…Treatment with DAAs reduces liver stiffness; however, this is negatively associated with an increase in the severity of fatty liver [ 77 , 78 ]. Co-existing fatty liver is also a risk factor for HCC after cure in patients with HCV infection [ 79 , 80 ]. Furthermore, Peleg et al [ 81 ] demonstrated that fatty liver is a major predictor of all-cause mortality in patients who achieve a sustained virological response following DAA treatment, regardless of fibrosis stage.…”
Section: Importance Of Multiple Etiologies Of Liver Disease: Mafld Vi...mentioning
confidence: 99%
“…The association between liver fibrosis and IFN‐λ3 levels shown in our results supports the possibility that IFN‐λ3 is induced during a fibrosis‐related immune response. In addition, there could be other causes of liver inflammation, such as liver steatosis or cellular senescence, as previously reported, although the association with liver fat or senescence‐associated secretory phenotypes was not evaluated in this study. Thus, it is possible that IFN‐λ3 might be induced by such chronic inflammation, which possibly promotes NHHN and HCC development after HCV clearance.…”
Section: Discussionmentioning
confidence: 83%
“…Yen et al demonstrated that in addition to age, fibrosis stage, HCV genotype 1, steatosis and DM, either alone or in combination, were independent factors associated with HCC development in patients with CHC who had achieved SVR after pegylated interferon‐based therapy. These findings suggest that the prevalent severity of liver fibrosis and MS‐related steatosis is crucial to the future risk of HCC after HCV is eradicated 34 . Age, AST‐to‐ALT ratio and platelet count are frequently used for predicting the severity of liver fibrosis, and these variables are also components of FIB‐4 19,35 .…”
Section: Discussionmentioning
confidence: 99%